Avaliação do tratamento do lixiviado do aterro sanitário de Maringá, Paraná, por processo de coagulação/floculação e ozonização - Pedroso, Keylla (2012)
Even if a sanitary landfill is a projected work within the technical parameters of engineering, this way of disposition is not totally capable to certify that there isn't damage for environment and health care system. It's because the disposition of urban solid waste in landfills brings as a consequence the formation of two sub products, gases and the leachate. The leachate is a dark liquid, highly toxic, of particular characteristic and diversified composition, because its generation depends on the anaerobic decomposition of buried waste and several physical, chemical and biological factors that occur in landfill. The contact of this effluent with water bodies and soil can bring great and negative consequences, as well as a potential form of pollution. So, this current survey's objective is to monitor the leachate of a sanitary landfill in Maringa-PR and evaluate treatment process, individualized and combined, aiming to improve its quality. The pre-coagulation/flocculation treatment with tanfloc SG®, accomplished in order to reduce the suspended solids and dissolved in liquid mass, presented good color removal up to 59,97% the turbidity up to 94,87% and absorbed compounds to 254nm up to 31,69%. Such values had been got when tests were developed with leachate pH adjusted to 9 and with elevated concentrations of coagulants (1100 and 1500 mg/L). The oxidative treatment with ozone was successful when tested different conditions of leachate in reaction times of 120 minutes. The best removals were found for ozonized leachate that was pre-treated for the coagulation/flocculation process with tanfloc SG*, reaching color removal up to 96,66%, the turbidity of 88,34%, the absorbed compounds to 254nm up to 85,11% and DQO 89% what confirms the efficiency to match the chemical-physical treatment with ozonization to treat this leachate.